Assessment and Optimization of Water Division Pattern in Sampean Baru Irrigation Area - Joice Prasasty September; Entin Hidayah; Gusfan Halik (U Karst, 2021)
Recently, agricultural production in the Sampean Baru Irrigation area has not shown optimal cropping production. The average percentage of planted areas in the first (November-February),second (March-June), and third (July-October) planting seasons for the upstream area was 93.67%; 98.02%, and 76.76%, and for the downstream area was 83.54%; 80.81%; and 89.36%. This research aims to optimize the water distribution system based on the calculation of water requirements for plants and the availability of channels to obtain the maximum planting area and amount of agricultural production. This optimization method uses a Dynamic Program with three scenarios. This calculation is based on effective rainfall, crop water requirements, and water discharge availability. Percentage of planted area obtained from the calculation in the dry year for the first, second, and third planting seasons respectively were 100%, 100%, and 90.36%. Based on the existing condition, potential profit obtained for a year is Rp. 170.08 billion. After optimization using Dynamic Program, potential profit in the dry year, normal year, and wet year are IDR 213.52 billion, IDR 215.92 billion, and IDR 228.50 billion, respectively.